PELAKSANAAN ANGGARAN PENERIMAAN DAN PENGELUARAN DANA DESA DALAM MENUNJANG PEMBANGUNAN DESA DI DESA TOMBULANG KECAMATAN PINOGALUMAN KABUPATEN BOLAANG MONGONDOW UTARA - Kristiani, Kristian; Pelleng, Frendy A. O.; Manopo, W. S. (Sam Ratulangi University, 2017)
This researce based on the importance of the invorvement of allelements of village administration in Tombulang village of North BolaangMongondow Regency, in maximizing village revenues sourced from villagefunds to support development. To that end, the village government mustunderstand how the implementation og budget of revenues and expenditures ofvillage fund in supporting development. This study aims to find out how theimplementation of budget revenue and expenditure of village funds in supportvillage development. Accourding to Government Regulation Number 60 year2014, Village funds are funds sourced from the State Revenue and ExpenditureBudget in the designated for the villages transferred through the RegionalRevenue Budgets and are used to finance the implementation of governance,development and community and community empowerment. This research useddescriptive qualitative research methods, data analysis techniques used in thisstudy is the percentage of data analysis. Informant research amounted to 3people and data collection technique is documentation study, interview, andobservation. The focus of the research is the accountability report of VillageRevenue and Expendeture year 2015 and 2016.The results show that the role of village funds in the development ofTombulang Village has been well realized although there are some things thatare unclear in the implementation of APBDesa and public participation and therole of government that has not been optimal. Briefly, the active role,tranparency and responsibility of the apparatus involvet in managing villagefunds is needed to support community development in the village and impact onthe welfare of the community. In this case the village government in demand tobe more involving the community in submetting the proposet plan ofpreparation of APBDesa and priotize the principle of honesty in order to avoidmisunderstanding.Keywords: Village Fund, Budeget, and Village Development